2011
DOI: 10.4161/epi.6.4.14531
|View full text |Cite
|
Sign up to set email alerts
|

MassSQUIRM

Abstract: In eukaryotes, DNA is wrapped around proteins called histones and is condensed into chromatin. Post-translational modification of histones can result in changes in gene expression. One of the most well-studied histone modifications is the methylation of lysine 4 on histone H3 (H3K4). This residue can be mono-, di-or tri-methylated and these varying methylation states have been associated with different levels of gene expression. Understanding exactly what the purpose of these methylation states is, in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…This assay is conducted for an extended time period utilizing a high LSD1 concentration, with conditions where LSD1-catalyzed demethylation of the H3-21-K4Me2 substrate nears completion, resulting in extensive conversion of the substrate to mono-and unmethylated H3-21. As reported previously, greater than 10 mM phenelzine is needed to extinguish LSD1 activity under MassSQUIRM conditions 50 . Thus, we compared 50 µM each of phenelzine and analogue 12d in an identical LSD1 inhibition MassSQUIRM assay.…”
Section: Resultssupporting
confidence: 71%
“…This assay is conducted for an extended time period utilizing a high LSD1 concentration, with conditions where LSD1-catalyzed demethylation of the H3-21-K4Me2 substrate nears completion, resulting in extensive conversion of the substrate to mono-and unmethylated H3-21. As reported previously, greater than 10 mM phenelzine is needed to extinguish LSD1 activity under MassSQUIRM conditions 50 . Thus, we compared 50 µM each of phenelzine and analogue 12d in an identical LSD1 inhibition MassSQUIRM assay.…”
Section: Resultssupporting
confidence: 71%
“…Several in vitro biochemical LSD1 enzymatic assays have been developed including HOOH detection through a peroxidase-coupled assay, formaldehyde detection through a formaldehyde dehydrogenase assay, radioactive measurements to monitor changes in a radiolabeled peptide substrate, and mass spectrometry analysis to measure changes in the unlabeled substrate (Blair et al, 2011; Forneris et al, 2005; Kokura, Sun, & Fang, 2015). In addition, cellular assays have been adapted to quantify LSD1-mediated effects on histone H3K4 methylation using antibody detection (Schmitt et al, 2014).…”
Section: Lsd1 Assaysmentioning
confidence: 99%
“…Several methods have been developed to address the methyl-Lys population states. One of these approaches involves the reductive methylation with heavy (dideuterio) formaldehyde to convert all states to the same chemical species such that there are no intrinsic ionization differences but the mass differences are detectable (Blair et al, 2011; Blair, Avaritt, & Tackett, 2012). This method, called MassSQUIRM, which uses MALDI-TOF (matrix-assisted laser desorption ionization-time-of-flight) is a highly quantitative technique and has been used to assess LSD1 inhibition (Blair et al, 2011).…”
Section: Lsd1 Assaysmentioning
confidence: 99%
“…There have been studies that attempted to quantify methylation by direct spotting, but to our knowledge no studies have reported kinetic analyses for peptide substrates, most likely because of the limited sensitivity. The MassSQUIRM technique has been developed to utilize isotopic enrichment to increase sensitivity, but requires deuterated formaldehyde to generate the substituted peptides [31]. …”
mentioning
confidence: 99%